A Clustered Randomized Trial of an Educational Intervention During Transplant Evaluation to Increase Knowledge of Living Donor Kidney Transplant. (December 2017) - Weng, Francis L.; Peipert, John D.; Holland, Bart K.; Brown, Diane R.; Waterman, Amy D.
Introduction: Maximizing education about living donor kidney transplant (LDKT) during the in-person evaluation at the transplant center may increase the numbers of kidney patients pursuing LDKT. Research Questions and Design: To test the effectiveness of a 1-time LDKT educational intervention, we performed a cluster-randomized trial among 499 patients who presented for evaluation of kidney transplant. We compared usual care education (n = 250) versus intensive LDKT education (n = 249), which was implemented only on the evaluation day and consisted of viewing a 25-minute video of information and stories about LDKT and discussion of LDKT possibilities with an educator. Our primary outcome was knowledge of LDKT, 1 week after the transplant evaluation. Results: One week after evaluation, patients who received intensive education had higher knowledge than patients who received usual care (12.7 vs. 11.7; P = .0008), but there were no differences in postevaluation readiness for LDKT. Among patients who had not previously identified a potential living donor, receiving intensive education was associated with increased willingness to take steps toward LDKT. Discussion: In conclusion, expansion of LDKT education within the evaluation day may be helpful, but interventions that are implemented at multiple times and for greater duration may be necessary to ensure larger and long-term behavioral changes in pursuit of LDKT.